Research goes commercial - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
A Centre for Agribusiness Services has been set up in the Caribbean region by the Caribbean Agricultural Research and Development Institute to support commercial activities in the private sector and to ensure business opportunities are exploited. It...